Globalization and equality: A cross-country analysis - Shujiro Urata; Youngmin Baek (Asian Development Bank Institute (ADBI), 2024)
Using a cross-sectional dataset of 13 manufacturing sectors in 27 Asian developing countries from 2008 to 2022, we investigated the impact of the presence of foreign firms on wages of workers from domestic firms. First, we found that the average wage of workers from foreign firms is higher than that of workers from domestic firms. This pattern is more pronounced in the cases of low-income countries and the service sector. Second, the average wage of workers from domestic firms that are exposed to foreign firms is higher than that of domestic firms without exposure to foreign firms, indicating a spillover of wages from foreign to domestic firms. Third, the presence of foreign firms is found to widen the wage gap between skilled and unskilled workers. Based on our findings, we argue that developing countries should improve their FDI environment to attract FDI and upgrade the quality of unskilled labor by providing education and training, in order to reduce the wage gap.
Keywords: D22; E24; F21; R1; 330; foreign direct investment; wage spillovers; wage inequality